2020
DOI: 10.3390/rs12152360
|View full text |Cite
|
Sign up to set email alerts
|

Application of Empirical Land-Cover Changes to Construct Climate Change Scenarios in Federally Managed Lands

Abstract: Sagebrush-dominant ecosystems in the western United States are highly vulnerable to climatic variability. To understand how these ecosystems will respond under potential future conditions, we correlated changes in National Land Cover Dataset “Back-in-Time” fractional cover maps from 1985-2018 with Daymet climate data in three federally managed preserves in the sagebrush steppe ecosystem: Beaty Butte Herd Management Area, Hart Mountain National Antelope Refuge, and Sheldon National Wildlife Refuge. Future (2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…4). Similar results were reported by Tietjen et al (2017) who found RCP 4.5 and 8.5 scenarios gave similar results globally, and by Soulard and Rigge (2020) in the northern Great Basin. Our data do show more dramatic changes in the RCP 8.5 scenario, however, with greater increases in shrub and bare ground, and more abrupt decreases in herbaceous cover and sagebrush cover (Fig.…”
Section: Rcp Scenario Comparisonsupporting
confidence: 89%
See 1 more Smart Citation
“…4). Similar results were reported by Tietjen et al (2017) who found RCP 4.5 and 8.5 scenarios gave similar results globally, and by Soulard and Rigge (2020) in the northern Great Basin. Our data do show more dramatic changes in the RCP 8.5 scenario, however, with greater increases in shrub and bare ground, and more abrupt decreases in herbaceous cover and sagebrush cover (Fig.…”
Section: Rcp Scenario Comparisonsupporting
confidence: 89%
“…Population models can be used to model the climate change impacts to sagebrush, but due to the nature of such observations and computational demands in modeling, population models tend to be applied at local scales (Tredennick et al 2016). Another approach is to apply empirical climate relationships observed in historical data with simulation software to evaluate the impact of diverging climate scenarios (Soulard and Rigge 2020). Finally, Homer et al (2015) extended linear correlations between rangeland fractional component cover and historical precipitation data to project cover given two climate scenarios in 2050.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high availability of data used in this study, climate simulations have inherent uncertainties about the future, and the types and patterns of projected changes may be the result of model parameterization processes [17]-detailed processes that need to be further explored by dynamically combining land and atmospheric modules at finer scales to better understand the relationship between the land surface and the atmosphere. In addition, there are unavoidable biases in the experimental design (e.g., boundary conditions, regional climate models, regions), and scenario assumptions can be adjusted and additional complexity considered.…”
Section: Strengths and Uncertaintiesmentioning
confidence: 99%
“…Additionally, assumptions on how LUCC would affect climate under RCP or SSP-based future scenarios have also been reported. For example, Soulard and Rigge [17] studied and analyzed changes in the abundance and distribution of vegetation cover under future climate change scenarios, i.e., Business As Usual (BAU) and Representative Concentration Pathway (RCP) 8.5 scenarios. The results of the study showed that the area of bare ground will decrease at pixel sites with high bare ground cover, herbaceous cover will also decrease at pixel sites with moderate herbaceous cover, and shrub cover will increase at pixel sites with low shrub cover.…”
Section: Introductionmentioning
confidence: 99%